1990
DOI: 10.1007/bf00228125
|View full text |Cite
|
Sign up to set email alerts
|

Somatotopic organization and columnar structure of vibrissae representation in the rat ventrobasal complex

Abstract: The region of vibrissae representation in the ventrobasal complex (VB) of the rat was systematically mapped, based on receptive fields of many single neurons. Results showed that the ventralmost row of vibrissae projected to the rostral part of VB, that the dorsal-most row projected to the caudal part, and that the caudalmost vibrissae of each row projected to the most dorsolateral part of VB and more rostral vibrissae to the more ventromedial part. Further, it was revealed that the clusters of neurons receivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 36 publications
6
35
0
Order By: Relevance
“…They were performed under different types and regimens of anesthesia, and among those that paid attention to receptive field size, three provided electrode tract reconstructions that registered the location of the recorded units (Rhoades et al, 1987;Ito, 1988;Sugitani et al, 1990). Two of these studies reported that VPM neurons with large receptive fields were more numerous dorsally, whereas cells with a single whisker receptive field were recorded deeper in vertical electrode penetrations through VPM (Ito, 1988;Sugitani et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…They were performed under different types and regimens of anesthesia, and among those that paid attention to receptive field size, three provided electrode tract reconstructions that registered the location of the recorded units (Rhoades et al, 1987;Ito, 1988;Sugitani et al, 1990). Two of these studies reported that VPM neurons with large receptive fields were more numerous dorsally, whereas cells with a single whisker receptive field were recorded deeper in vertical electrode penetrations through VPM (Ito, 1988;Sugitani et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…6, apical vs. basal). Recently, the present author (Ito, 1988) has reported that transient-and sustained-type neurones in the thalamic ventral posteromedial nucleus have a mean RF of 4-3 and 1-6 respectively in terms of the number of whiskers (see also Sugitani, Yano, Sugai & Ooyama, 1990;. The apparent discrepancy between the receptive field size and the dendritic field size can be explained by supposing that the multi-whisker transient-type thalamic neurones project to the multi-whisker transient-type pyramidal neurones in layer 5b.…”
Section: Tangential Sectionsmentioning
confidence: 92%
“…whisker receptive fields (Sugitani et al 1990), and thalamocortical cells that fire more robustly to adjacent whiskers also respond more robustly to the principal whisker (Bruno and Simons 2002). Similarly, the slowest conducting, longest latency, and weakest responding TCUs might be preferentially situated in the ventrolateral aspects of VPm where neurons may receive longer-latency inputs from the spinal trigeminal complex as well as from PrV (Pierret et al 2000).…”
Section: Bmentioning
confidence: 99%